Intensifikasi Pemungutan Pajak Bumi Bangunan Pedesaan dan Perkotaan dalam Upaya Peningkatan Pendapatan Asli Daerah di Kabupaten Lampung Utara - Alfis Syahrin; Syamsul Ma’arif; Nana Mulyana (Jurnal Administrativa, 2020)
Intensification (PBB-PP) is a policy implemented by the North Lampung Regency (BPPRD) to maximize revenue from the local tax sector. This study uses the concept indicators of the implementation of the intensification process of PBB-PP collection and inhibiting and supporting factors in the intensification process of PBB-PP collection in North Lampung Regency to produce optimal realization outcomes. The method used in this study is a type of descriptive research with a qualitative approach. This study aims to determine and examine what factors make the realization of PBB-PP revenue in North Lampung Regency optimal. Based on research conducted, the results obtained are the implementation of this intensification has been going well. This research is said to have been very good because Implementation of the intensification program made by BPPRD in the context of maximizing PBB-PP revenue are arguably quite maximal related to revenue (PBB-PP) in North Lampung. The main factor that greatly influences the optimal acceptance of PBB-PP in North Lampung Regency is the Fiscus Performance in carrying out services, supervision and collection running well because it is supported by the quality of professional human resources and supported by the use of a technology -based progress system so that taxpayers who feel the way to pay taxes are to develop a sense of awareness of their obligations to pay taxes. Keywords: Intensification, Collection, Realization, Tax.